Pengembangan Produk dan Strategi Pemasaran Online Pada UMKM di Desa Tlajung Udik - Ayuningtias, Putri; Nadiva, Vina Maharani; Rahmah, Annuriah; Tuzzahra, Sakila; Yusup, Putri Meida; Sari, Nita Puspita; Nuraini, Syaila; Riyanto, Sugeng; Usman , HM (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2025)
The Real Work Lecture (KKN) program is a form of community service that aims to integrate students' academic abilities with real needs in the field. This activity was carried out by STEBIS Bina Mandiri students in May 2025 in Tlajung Udik Village, with a focus on empowering Micro, Small and Medium Enterprises (MSMEs) called Dapur Syafar which is engaged in home culinary. The main problems identified include the absence of halal certification, unattractive product packaging, and lack of digital literacy in marketing. The implementation method uses participatory research with a descriptive quantitative approach. One of the main interventions is the analysis of the Cost of Goods Produced (COGS) of packaged chili sauce, which includes raw material costs, direct labor, and overhead costs. The calculation results showed that the COGS per bottle was Rp. 20,000 with a selling price of Rp. 25,000, providing a 25% profit margin. In addition, a new logo, packaging, halal certification, and TikTok Shop account activation as an online marketing medium were carried out. The results showed significant improvements in product appearance, sales turnover, and business involvement in digitalization. Thus, this KKN program established an adaptive, collaborative, and sustainable MSME mentoring model.